2017
DOI: 10.3390/su9030391
|View full text |Cite
|
Sign up to set email alerts
|

Social Surveys about Solid Waste Management within Higher Education Institutes: A Comparison

Abstract: Abstract:Solid waste mismanagement is a social burden that requires the introduction of reliable public policies, including recycling principles and technological facilities. However, the development of recycling plans is a real issue for municipal governments, since it involves psychological and cultural factors, both in developed and developing countries. Questionnaire survey is an important tool for evaluating which solid waste management policy is suited for each specific study area, involving citizens and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 59 publications
4
15
0
1
Order By: Relevance
“…The users of the GP are 3–13% of the population (H4), while about 49% of the citizens implement the SC at home (H5). These results are in agreement with a previous study conducted at the Salesian University of La Paz where 57% of the students stated that they separate the waste at home (Ferronato et al, 2017). Again, this behaviour has not dependence with the SES.…”
Section: Discussionsupporting
confidence: 93%
“…The users of the GP are 3–13% of the population (H4), while about 49% of the citizens implement the SC at home (H5). These results are in agreement with a previous study conducted at the Salesian University of La Paz where 57% of the students stated that they separate the waste at home (Ferronato et al, 2017). Again, this behaviour has not dependence with the SES.…”
Section: Discussionsupporting
confidence: 93%
“…As an example, multiple studies found that there are differences in attitude towards waste sorting between younger and older generations [26][27][28] while others concluded that age does not impact participation in sorting [29]. Social surveys conducted in higher education institutes in developing countries found that sixty percent of surveyed students in Bolivia participate in waste sorting by sorting up to half of their household waste, even though recycling rates are generally low [30]. Whereas, roughly half of the students who participated in a survey in China claimed to sort their waste despite much higher participation rates among their parents (around one in three) [31].…”
Section: Introductionmentioning
confidence: 99%
“…The collection is guaranteed, on average, two times per week, depending on the area. It is common that the collection service is applied more than three times per week in the city center, while in suburban areas it is not applied at all (Ferronato et al, 2017b). This method is not adequate for guaranteeing the street cleaning and public hygiene due to foul smell and proliferation of flies and other vectors.…”
Section: Results—physical Components Of Mswm System In La Pazmentioning
confidence: 99%